Autism Spectrum Disorder (ASD) Therapy in the Era of the Covid-19 Pandemic - Faadhilah, Aisyah; Prasetya, Era Catur; Dinata, M. Thoriq Satria; Rohmah, Lina Nur Hidayahtur; Nerly, Wichda Shirosa; Prastya, Aldo Dwi; Abiola, Tajudeen (Universitas Muhammadiyah Semarang, 2022)
Background: Autism Spectrum Disorder is a common neurodevelopmental disorder with a reported prevalence in the United States of around 1.7%. The core deficits of ASD were identified in 2 domains: social communication/interaction and restrictive, repetitive behavior patterns. Children and adolescents with ASD have service needs in behavior, education, health, recreation, family support, and other areas. For individuals with autism spectrum disorders, school and therapy services can serve various essential functions, from delivering academic instruction to developing effective communication and building social skills.Objective: This study is to examine ASD during the COVID-19 pandemic. The researcher has emphasized the importance of specific therapies for children with ASD and has repeatedly shown their association with positive outcomes across various skill domains.Method: The literature review is processed based on academic journals published on Science Direct, PubMed, and Google Scholar, from 2019 to 2020.Results: The study found various methods and learning methods for children with ASD in the COVID-19 pandemic.Conclusion: Many obstacles have been overcome for children with ASD and therapists during the COVID-19 period. Suggestions and tips for parents and therapists to take further action on children.